دافع تعلّم المحادثة لدى التلاميذ فى الفصل الثانى بمدرسة " الحكمة" الثانوية اﻹسلامية فاسير مجين دماك - Ulwi Albab (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2020)
This study seeks to find out whether differences in Muhadatsah's Learning Motivation were found for second-grade students (VIII) at the ‘Al-Hikmah’ Tsanawiyyah Al-Islamiyah Pasir Mijen Demak Madrasah between students graduating from MI and students graduating from elementary school. The approach article used in this research is a quantitative approach because the researcher wants to test the hypotheses that are formed associative hypotheses (are hypotheses that ask for a relationship between two or more variables). This approach is said to be a quantitative approach because the existing data in the form of numbers and statistics are used in analyzing it. While the method used is Correlation Research, because correlation study researchers want to uncover the correlation of variations in correlation coefficients. The results of this study are: 1). There is an important difference in the degree of motivation for learning the conversation between the graduating students in the Islamic primary school and the graduating students in the public elementary school at the "Al-Hikmah" Islamic secondary school, Pasir Majin Demak. Here we know this indication from the value of "to" and the value of "tt". From the previous accounting it is known that "to" is greater than "tt", meaning: 2,68> 4,911 <2,01. These indicate that students who graduated from an Islamic elementary school have a strong motivation for learning conversation because the students who graduated from an Islamic elementary school have learned conversation in the Arabic language in order to motivate them to strive in learning and because the Arabic language without the lesson is strange to it.